Establishing Shrubs in Florida Landscapes - Edward F. Gilman; Amy L. Shober; Kimberly A. Moore; Christine Wiese; Maria Paz Kinslow; S. Michelle Scheiber (EDIS)
ENH-1130, a 6-page illustrated fact sheet by Edward F. Gilman, Amy L. Shober, Kimberly A. Moore, Christine Wiese, Maria Paz, and S. Michelle Scheiber, describes the steps that homeowners should take for effective irrigation of transplanted, container-grown shrubs in the home landscape until there is sufficient root growth for them to become established. Includes additional resources. Published by the UF Department of Environmental Horticulture, June 2009.